Komunikasi Visual Destination Branding Kecamatan Lasem Kabupaten Rembang Sebagai Cagar Budaya - Celestapasha, Humaira Asoka (Besaung : Jurnal Seni Desain dan Budaya, 2025)
Lasem is not yet fully recognized as having an image as a national cultural heritage asset, even though it has a legacy of rich history and culture. Many people, especially the younger generation, do not know or are interested in preserving the importance of the Lasem cultural heritage. Designing destination branding through a visual communication design approach is a concept proposed as an action to raise public appreciation and level of awareness of the existence of the Lasem cultural heritage. This research uses the design thinking design method with the process stages of empathize, define, ideate, prototype and test. At the ideate stage, information is obtained through the results of Charles S Pierce's semiotic analysis. The results of designing destination branding using a visual communication design approach are in the form of a brand guideline book entitled Kesengsem Lasem, containing the visual identity of the Lasem cultural heritage. Through this design, it is hoped that it will be able to increase awareness and appreciation of the younger generation towards the existence of cultural heritage in Lasem.